Mobile Game Prototype for Fractional Concept in Elementary School - Anggraeni Maharbid, Dian Anggraeni Maharbid; Herman, Tatang; Setiawan, Wawan (KnE Social Sciences, 2024)
This research aims to create a prototype of a mobile game that can be used as an instructional media for mathematics learning in school and then test the effectiveness of the product for the result. This research uses the research and development (R&D) method with the subject of research being 35 students of the third-grade elementary school in Cirebon. The process of creating mobile game prototypes consists of analyzing the user’s needs, prototype design, trial and error, evaluation and revision, validation, implementation, and the final result of a prototype. In analyzing a user’s needs the following steps were included, analysis of the curriculum, content, concepts, and characteristics of users, in this case, are 3rd-grade students in elementary school. The main content of this research is fraction concepts such as knowing their concept, the symbols, comparing fractions, their equal value, sorting fractions, and adding or subtracting fractions with the same denominator. All the analysis was put into prototype design to create flowcharts, storyboards, and interfaces. The results of the prototype design were then tested by trial and error on small samples. After revision, the final prototype then got validation from expert judgment with notes that can be implemented. Keywords: elementary school, fractional concept, mobile game